2020
DOI: 10.18502/sjms.v15i3.7013
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Blood Groups in Patients with Angiographically Defined Coronary Artery Disease in Iranian Community

Abstract: In the past, the relationship between coronary artery disease (CAD) and been studied extensively. The ABO blood group has a significant effect on homeostasis and is therefore associated with adverse cardiovascular events. This study aimed to determine the distribution of ABO blood group and rhesus (Rh) status (ABO/Rh) in patients with different severity of CAD in Iranian community. A total of 1,236 CAD patients undergoing angiography were evaluated and their ABO/Rh blood type was determined in a study center b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(20 reference statements)
1
0
0
Order By: Relevance
“…A study conducted by Celebi et al evaluated the association between blood group types and the development of coronary collateral circulation in 212 patients with CAD and reported that poor collateral development is associated with non-O blood group type 17 . However, like our findings, a study by Rasmi et al in an Iranian population also observed no association between the number of diseased vessels and ABO distribution of blood group 18 . When ABO distribution was studied for association with thrombus burden in 369 patients with ST-segment elevation myocardial infarction (STEMI) by Askin et al, no relationship with thrombus burden and ABO blood type was noted 19 .…”
Section: Resultssupporting
confidence: 76%
“…A study conducted by Celebi et al evaluated the association between blood group types and the development of coronary collateral circulation in 212 patients with CAD and reported that poor collateral development is associated with non-O blood group type 17 . However, like our findings, a study by Rasmi et al in an Iranian population also observed no association between the number of diseased vessels and ABO distribution of blood group 18 . When ABO distribution was studied for association with thrombus burden in 369 patients with ST-segment elevation myocardial infarction (STEMI) by Askin et al, no relationship with thrombus burden and ABO blood type was noted 19 .…”
Section: Resultssupporting
confidence: 76%